IILL-POSED PROBLEM OF RECONSTRUCTION OF THE POPULATION SIZE IN THE HUTCHINSON–WRIGHT EQUATION - Yurii F. Dolgii; Platon G. Surkov (Ural Mathematical Journal)
We consider an ill-posed problem of reconstruction of the population size in the Hutchinson – Wright Equation. Regularized solutions were constructed on the finite interval of the negative half-line.